The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1115/1.3247425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fin Spacing on the Performance of Horizontal Integral-Fin Condenser Tubes

Abstract: The dependence of heat transfer performance on fin spacing has been investigated for condensation of steam on horizontal integral-fin tubes. Thirteen tubes have been used with rectangular section fins having the same width and height (0.5 mm and 1.6 mm) and with fin pitch varying from 1.0 mm to 20.5 mm. For comparison, tests were made using a plain tube having the same inside diameter and an outside diameter equal to that at the root of the fins for the finned tubes. All tests were made at near-atmospheric pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 0 publications
0
51
0
Order By: Relevance
“…For both larger and smaller diameters, the best-performing integral-fin tubes were found with fin spacings of 1.5, 1.0 and 0.5mm for steam, ethylene glycol and R-113, respectively. They compared their own experimental data with the indirectly obtained experimental data of earlier investigators [24,27,28,30] and a satisfactory agreement was found.…”
Section: Tubes With Two-dimensional Finsmentioning
confidence: 64%
See 2 more Smart Citations
“…For both larger and smaller diameters, the best-performing integral-fin tubes were found with fin spacings of 1.5, 1.0 and 0.5mm for steam, ethylene glycol and R-113, respectively. They compared their own experimental data with the indirectly obtained experimental data of earlier investigators [24,27,28,30] and a satisfactory agreement was found.…”
Section: Tubes With Two-dimensional Finsmentioning
confidence: 64%
“…The saw-toothed tube gave the best heat-transfer enhancements (defined as heat-transfer coefficient for saw-toothed tube based on fin-tip diameter divided by the heat-transfer coefficient for a smooth tube at the same vapour-side, temperature difference) for both fluids which was 9.0 and 6.1 for R-113 and methanol, respectively. Yau et al [24] reported an experimental study of dependence of heat transfer on fin spacing for the condensation of steam on horizontal integral-fin tubes. Thirteen tubes with rectangular fins having a thickness of 0.5mm and a height of 1.6 mm were tested by systematically varying fin spacing from 0.5 to 20mm.…”
Section: Tubes With Two-dimensional Finsmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments, either the heat transfer was measured using single tubes [25, 26, 31-34, 36, 37, 42, 43, 46, 51, 54, 55, 57, 58] and tube bundles [12,20,22,28,45,[47][48][49][50]56], or capillary phenomena and condensate retention in the lower bottom tube region [31][32][33][34]37] were analysed. As was to be expected, flooding of the lower tube portion is influenced by fin geometry and physical properties of condensate.…”
Section: Current Publicationsmentioning
confidence: 99%
“…A significant number of experimental investigations have been reported on free-convection condensation heat-transfer on horizontal integral-fin tubes; see for example [1][2][3][4][5][6][7][8][9][10][11]. During the condensation process, liquid retained on the lower part of tube insulates the fin flanks and root from heat transfer, This condensate retention on integral-fin tubes was first observed by Katz et al [12] and afterwards experimentally investigated by many other investigators for a wide range of fluid and tube combinations [1,3,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%